Colouring Emotions: Accompanied Keyboard Sonatas on the Fortepiano and Flute - Zafeiropoulos, Anastasios (Matera, Italy Duni Festival, 2024)
Programm:Johann Schobert (ca. 1720–1767): Accompanied keyboard sonata Eb Op. 7 No. 1Allegro moderato – Minuetto – Allegro assai (arr. Vera Plosila & Anastasios Zafeiropoulos)Carl Philipp Emanuel Bach (1714–1788): Rondo C Minor Wq.59 (für Kenner und Liebhaber)Johann Christian Bach (1735–1782): Accompanied keyboard sonata A major Op. 17 No. 4Allegretto – Pastorale. Non tanto allegroC.P.E. Bach: Flute Sonata A Minor H. 562Poco adagio – Allegro – AllegroMuzio Clementi (1752–1832): Accompanied keyboard sonata F major Op. 2 No. 5Allegro moltissimo – AllegrettoVera Plosila, traversoAnastasios Zafeiropoulos, fortepiano
In accompanied sonatas, melody instruments like the flute play an optional, often improvised, lines to pre-existing keyboard pieces. This was a short-lived genre at the end of the 18th century, but an extremely popular past time among amateurs who articulated their friendships and family bonds through chamber music. In general, music was seen as the appropriate medium to express affects, or emotions, and the essence of instrumental music was closely tied to the imitation of nature and these emotional states.The relationship to musical works was different from our time, as pieces were not yet seen as untouchable masterpieces but more like starting points for performance. As long as the music maintained its core invention, and was treated with good taste, musicians and music lovers saw no issue in altering and recycling materials. In our research concert tonight, we ask how much can be recomposed and rearranged while still sustaining the original musical ideas of the pieces performed.The program focuses on repertoire from German regions, but influences travelled in central Europe, and the pieces could be more easily understood under the umbrella of the galant style. Johann Schobert was a German, who resettled in Paris and explored the idiom of accompanied sonatas. Bach’s sons Carl Philipp Emanuel and Wilhelm Friedemann made their livelihood in Germany following the empfindsamer Stil, or the ‘sensibility style’ which focused on intimate inflections of affects and was greatly influenced by English literature. Their little brother Johann Christian studied and worked in Italy and became subsequently a celebrated composer in England. Muzio Clementi was a Roman who resettled in London and is known nowadays as an early proponent of the piano.The Fortepiano was a novelty of the late 18th century and hailed for its capacity to ‘sing’, to sustain a melody, and to express a broad range of dynamics and colours. It was the subject of experimentation and innovation – as much as the music written for it, in the quest to illustrate emotional experience.
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850